2017
DOI: 10.1155/2017/7604861
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Phototherapy on Cancer Predisposition Genes of Diabetic and Normal Human Skin Fibroblasts

Abstract: The purpose of this study was to investigate whether LED light at different wavelengths affects the expression profile of 143 cancer predisposition genes in both diabetic and normal human fibroblasts. In this study, both diabetic and normal fibroblast cell lines were cultured and irradiated with red (635 nm), green (520 nm), and blue (465 nm) LED light for 10 minutes at 0.67 J/cm2 each. After that, mRNA from all cell lines was extracted for microarray analysis. We found that green light activates EPHB2, KIT, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Interestingly, this sharp reduction in retinal PDE11A4 expression coincides with the approximate period when mice open their eyes for the first time (P10-13). This correlation is particularly interesting given a report showing that light exposure can regulate PDE11A4 expression in vitro [32]. In contrast, we observed a gradual age-related increase in PDE11A4 expression in the anterior segment (Figure 2B), which would reduce cAMP and cGMP.…”
Section: Pde11a4 Expression In the Eye Changes With Age In A Segment-...supporting
confidence: 63%
See 1 more Smart Citation
“…Interestingly, this sharp reduction in retinal PDE11A4 expression coincides with the approximate period when mice open their eyes for the first time (P10-13). This correlation is particularly interesting given a report showing that light exposure can regulate PDE11A4 expression in vitro [32]. In contrast, we observed a gradual age-related increase in PDE11A4 expression in the anterior segment (Figure 2B), which would reduce cAMP and cGMP.…”
Section: Pde11a4 Expression In the Eye Changes With Age In A Segment-...supporting
confidence: 63%
“…Although the presence of PDE11A protein has not yet been reported in the eye, its presence has been implied by human single-cell RNA sequencing studies [24][25][26][27][28]. Further, myopic development is associated with inadequate exposure to light [13,29,30], photo-transduction is highly dependent on hydrolysis of the PDE11A substrate cGMP [31], and specific wave lengths of light that upregulate PDE11A expression in fibroblast cells [32] demonstrate promise as potential anti-myopic agents [29]. Of particular interest to the fact that PDE11A-Y727C is both protective against myopia and enhancing to sleep quality, myopia has been associated with reduced sleep quality [33,34] and a dysregulated retinal circadian clock [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that blue light at lower doses (≤300 mJ/cm 2 ) triggers the synthesis of hydrogen peroxide in T-cells and affects cell motility [1]. Other studies suggest that blue light changes the redox state of the cell causing oxidative stress and alter mitochondrial activity [2,3] or that green light can change gene expression [4]. As recent technological advances brought televisions, LEDs, and displays, blue light emitters have become a part of our everyday life and blue light is also used for polymerization of dental resin in dentistry [5], its effect on the behavior of cells should be deeply studied.…”
Section: Introductionmentioning
confidence: 99%